The Evolution of Sensing Device for the Detection of Histamine and other Biogenic Amines - Khairiah Haji, Badri; Muhammad Abdurrahman, Munir; Lee, Yook Heng (Lupine Publishers, 2022)
This paper reviewed the progressive trend in the sensing of biogenic amine such as histamine. A sensor was developed where this sensor is using palm-based polyurethane as an electro-sensor substrate. Palm based polyurethane (PU) was produced via condensation polymerization between palm kernel oil-based monoester polyol (PKOp)and 4,4’-diphenylmethane diisocyanate (MDI). PU is used in this study due to its porosity and its capability to attach onto screen – printed electrode (SPE) sturdily without disintegrate. PU – SPE absorbed histamine inside its pores so histamine can undergo the oxidation process. The oxidation process was detected using cyclic voltammetry (CV) and differential pulse voltammetry (DPV).